"Poczuła ziemię pod całymi stopami". Przyroda w "Lecie" Tove Jansson: "She felt the earth beneath her whole feet". The Nature in "The Summer Book" by Tove Jansson - Budzanowska-Weglenda, Dominika (Colloquia Litteraria, 2024)
Tove Jansson, nicknamed the “Mummy of the Moomins”, wrote her novel The Summer Book in 1972, when she was already an established painter, illustrator and writer, especially of children’s novels. Nature proves to be an important background, not so much as the character of this story about the unique relationship between an eighty-year-old heart patient grandmother and her six-year-old granddaughter Sophie. The novel is set on a Finnish island, which is closely linked to Tove Jansson’s biography and personal experience. The author was well acquainted with the beauty and horror of nature from her autopsy. Nature in The Summer Book reflects and co-creates the moods, experiences and reflections on life, passing, death, God or love of the novel’s main characters.